In vitro selection of human rhinovirus relatively resistant to soluble intercellular adhesion molecule-1. - Arruda, E (1994)
Variants of human rhinovirus serotype 39 (HRV-39) relatively resistant to inhibition by soluble intercellular adhesion molecule-1 (sICAM-1) were selected by serial passages in HeLa or WI-38 cells in the presence of sICAM-1. Moderate resistance (four- to fivefold increases in 50% effective inhibitory concentrations [EC50s]) was observed after the second passage in HeLa cells and remained constant during six further passages in the presence of 10 micrograms of sICAM-1 per ml. A 7- to 17-fold increase in EC50s was observed in WI-38 cells during passage with 10 micrograms/ml, and reversion to a nonresistant phenotype was not observed after four passages in the absence of sICAM-1. Resistance of a higher degree was obtained by passing HRV-39 in the presence of 100 micrograms of sICAM-1 per ml in HeLa cells (30-fold EC50 increase). The sICAM-1-resistant phenotype was estimated to constitute 1 in 10(4) to 1 in 10(5) PFU of a nonexposed HRV-39 population. Low to moderate levels of resistance to sICAM-1 inhibition emerge readily during in vitro passage in the presence of sICAM-1 and appear to be phenotypically stable.